Skin Entrapment in an Un-displaced Proximal Humerus Fracture Treated with Closed Reduction; A Case Report - Hughes, Michael (Open Orthop J, 2016)
BACKGROUND: Proximal humerus fractures are a common presentation to Orthopaedic services in the United Kingdom, and the incidence is increasing. Proximal humerus fractures are usually associated with low energy trauma in elderly patients. There is a sub-set of younger patients who suffer low energy fractures due to underlying osteopenia, commonly associated with alcohol excess. Skin puckering or dimpling has been described as a very rare complication of proximal humerus fracture. Based on the few previously published reports of this complication, skin entrapment in proximal humerus fracture is usually predictive of failure of closed reduction, and need for open surgery. METHODS: Literature searches were carried out for relevant keywords. Articles were then critically appraised before being included in the literature review. RESULTS: The Authors were only able to identify three previous reports of this rare complication. CONCLUSION: The authors describe a rare case of skin interposition in an un-displaced proximal humerus fracture, outline a technique for closed reduction, and review the current literature surrounding this rare complication.